Ghost modes and continuum scattering in the dimerized distorted kagome lattice antiferromagnet Rb 2 Cu 3 SnF 12 - K. Matan (2018)
High-intensity pulsed neutron scattering reveals a new set of magnetic excitations in the pinwheel valence-bond solid state of the distorted kagome lattice antiferromagnet Rb2Cu3SnF12. The polarization of the dominant dispersive modes (2meV<â ω<7meV) is determined and found consistent with a dimer series expansion with strong Dzyaloshinskii-Moriya interactions (D/J=0.18). A weakly dispersive mode near 5 meV and shifted "ghosts" of the main modes are attributed to the enlarged unit cell below a T=215 K structural transition. Continuum scattering between 8 and 10 meV might be interpreted as a remnant of the kagome spinon continuum [Nature (London) 492, 406 (2012).NATUAS0028-083610.1038/nature11659]. © 2014 American Physical Society.